(untitled) (Лучшие интеллектуальные исследования, 2025)
Pregnancy represents a unique physiological state where both the mother’s and the developing fetus’s nutritional needs are heightened. Adequate nutrition during pregnancy is crucial for ensuring the optimal development of the fetus and maintaining the health of the mother. Among various nutrients, vitamins play a fundamental role in fetal growth and development. Pregnant women often require increased amounts of certain vitamins to meet the demands of pregnancy, as well as to prevent potential complications like neural tube defects, anemia, and impaired fetal development.